Miniaturized near-infrared instruments in dairy products or dairy industry: First steps in a long-distance race?. Issue 1 (March 2021) - Riu, Jordi; Gorla, Giulia; Giussani, Barbara
Near-infrared spectroscopy using benchtop instrumentation is widely used in the analysis of dairy products or in the dairy industry. In this paper, we review the use of miniaturized near-infrared instrumentation in dairy products or in the dairy industry, highlighting some strengths and limitations of current devices.